Flagellar-based motility accelerates IgA-mediated agglutination of Salmonella Typhimurium at high bacterial cell densities - Lindberg, Samantha K.; Willsey, Graham G.; Mantis, Nicholas J. (Frontiers in Immunology, 2023)
Secretory IgA (SIgA) protects the intestinal epithelium from enteric pathogens such as Salmonella enterica serovar Typhimurium (STm) through a process known as immune exclusion, where invading bacteria are aggregated via antibody cross-linking, encased in mucus, and then cleared from the intestinal tract via peristalsis. At high cell densities, the STm aggregates form a tightly packed network that is reminiscent of early bacterial biofilms. However, the underlying mechanism of how SIgA mediates this transition from a motile and invasive state to avirulent sessility in STm is currently unknown. In this report, we developed and validated a methodology known as the “snow globe” assay to enable real-time imaging and quantification of STm agglutination by the mouse monoclonal IgA Sal4. We observed that agglutination in the snow globe assay was dose-dependent, antigen-specific, and influenced by antibody isotype. We determined that flagellar-based motility was a prerequisite for rapid onset of agglutination, even at high cell densities where cell-cell contacts are expected to be frequent. We also investigated the roles of individual cyclic-di-GMP metabolizing enzymes previously implicated in motility and biofilm formation in Sal4 IgA-mediated agglutination. Taken together, our results demonstrate that IgA-mediated agglutination is a dynamic process influenced by bacterial motility and cell-cell collisions. We conclude that the snow globe assay is a viable platform to further decipher the molecular and genetic determinants that drive this interaction.